Utilizing rapid prototyping 3D printer for fabricating flexographic PDMS printing plate - Maksud, M. I.; Nodin, M. N.; Yusof, M. S.; Hassan, S. (Asian Research Publishing Network (ARPN), 2016)
Recently printed electronic field is significantly growth. Printed electronic is to develop electrical devices by printing method. Conventional printing method that has been studied for this kind of printed electronic such as flexographic, micro contact printing, screen printing, gravure and ink jet. In flexographic and microcontact printing, a printing plate is used to transfer the designed and desired pattern to substrate through conformed contact. Therefore printing plate is play a big role in this area. Printing plate making by photopolymer which used in flexographic have limitation in achieving a micro-scale of pattern size. However, printing plate of microcontact printing have an advantages in producing micro, even nano-scale size by PDMS (Polydimethylsiloxane). Hence, rapid prototyping 3D printer was used for developing a PDMS micro-scale printing plate which will be used in reel to reel (R2R) flexographic due to high speed, low cost, mass production of this type of printing process. The flexibility of 3D printer in producing any shape of pattern easily, contributed the success of this study. A nickel plating and glass etching master pattern was used in this study too as master pattern mould since 3D printer has been reached the micro size limitation. The finest multiple solid line array with 1mm width and 2mm gap pattern of printing plate was successfully fabricated by 3D printer master mould due to size limitation of the FDM (Fused Deposition Modeling) 3D printer nozzle itself. However, the micro-scale multiple solid line array of 100micron and 25micron successfully made by nikel platting and glass etching master mould respectively. Those types of printing plate producing method is valueable since it is easy, fast and low cost, used for micro-flexographic in printed electronic field or biomedical application.